FEASIBILITY AND ACCEPTANCE OF IMTOP INTERVENTION WITH RECENT CHINESE IMMIGRANTS IN LOS ANGELES: A PILOT STUDY. (11th November 2018) - Yu, K; Wu, S; Chi, I
Abstract: Recent immigrants are more likely to suffer a significant burden of chronic illnesses. This pilot study adopts a mixed-method approach with quantitative survey and in-depth interviews to test feasibility of using IMTOP intervention to facilitate diabetes self-management among recent Chinese immigrants with type 2 diabetes in Los Angeles (LA). Fifty-seven questionnaires were collected (mean age 62.71, 36.11% male, 71.43% reported English proficiency as "poor" or "fair"). The participants have experience using computer, tablet and smartphone at different rates, respectively, 43.75%, 52.67%, and 80.60%. Only half of the sample had diabetes self-management training previously and the majority (85.71%) of them rate the training helpful. Nine interviews were conducted to examine acceptance and seek suggestions to improve the intervention. Eight out of nine interviewees reported their willingness to participate IMTOP intervention and using the app. Participants suggested modifying the intervention to be compliant with lifestyles in LA and tailor to Chinese subcultures.